К вопросу о создании электронной медицинской карты больного сахарным диабетом - Носова, Т. В.; Жемчужкина, Т. В.; Филимончик, Д. В. (ХНУРЭ, 2008)
The given work is devoted a process of patient’s data registration and storage. In report is considered creation of electronic medical sheet for a patient with diabetes mellitus on the base of a database system. Database structure was designed on the base of analyses of data required to be stored in medical sheet of diabetes patient. For interaction with this database was designed web-interface for access to data by the computer net from any médical institution. Product appliance area are clinics, hospitals, diabetes research institutes
Keywords: электронная медицинская карта; сахарный диабет